Faktor Yang Berhubungan Dengan Kejadian Infeksi Saluran Kemih Pada Usia 15-18 Tahun di SMAN 11 Makassar (Window of Public Health Journal, 2025)
A urinary tract infection (UTI) occurs when the urinary system experiences an infection. Which generally attacks two parts, namely the urethra and the bladder. The World Health Organization (WHO) reports 8.3 million cases of UTI each year, making it the second most common infectious disease in the body after respiratory tract infections. In society, the rate of urinary tract infections increases with age. More than 13,000 people (2.3 percent of deaths) suffer from urinary tract infections, according to a survey in hospitals in the United States. The risk of urinary tract infection in people over 65 is 20%. UTI is a health problem that threatens millions of people every year. According to estimates from the Indonesian Ministry of Health, the number of UTI cases in Indonesia ranges from 90 to 100 cases per 100,000 people per year, or around 180,000 new cases per year. Adults usually suffer from UTIs, but teenagers can also suffer. This study aims to obtain information about factors related to the incidence of urinary tract infections in 15-18 year olds at SMAN 11 Makassar. This research will be conducted in SMA Negeri 11 Makassar. The Lemeshow formula was used to calculate the sample size, and a sample size of 96 people was obtained. Data analysis used univariate and bivariate analysis with the chi-square test. The results of the bivariate analysis based on the results of statistical tests showed that there was no significant relationship between sitting time (0.463> 0.05), perineal hygiene (0.671> 0.05), Hand Hygiene (0.588> 0.05), and Clothing Hygiene (0.633> 0.05) on Urinary Tract Infection Incidence Factors—suggestions for conducting massive socialization regarding the dangers of Urinary Tract Infection that can affect the younger generation.